Dança e a proposta da transdisciplinaridade na Educação - Marcilio de Souza Vieira (EccoS – Revista Científica)
The dance as a form of knowledge, while a sensitive education transforms and is transformed within school, as one of the ways of education of the body creator and critic. The role of the school turns it into educational processes that encourages the student possibilities and opportunities to enjoy it, contextualizes it and experience it in school. Lately it is the intrinsic relationship between knowledge of dance in the Arts in Physical Education, in history, geography, biology, finally, in the various areas of knowledge of basic education but also in the Transverse Themes covering various dances as a proposition. This paper intends to suggest indicative proposals for the construction of trans in the dance area, as well as reflect how dance can contribute to the various areas of knowledge of Basic Education. This work has the methodological approach of content analysis.